Threshold Dynamics Of Investor Overconfidence And Trading Activity: Evidence From Indonesia’s Stock Market - Emily, Lindsay Carnelian; Lestari, Reni (Jurnal Locus Penelitian dan Pengabdian, 2025)
This research explores the threshold dynamics of investor overconfidence in the Indonesian equity market using daily data from firms comprising the IDX80 (2015-2024). We proxy for overconfidence using excess turnover and analyze it with fixed-effects panel regression, and with Hansen's (1999) panel threshold model. We found that excess turnover significantly affects trading activity, the lagged returns reinforced self-attribution bias, and the smaller or undervalued firms primarily garnered speculative trading. The threshold analysis revealed regime dependency: firm-specific returns exceeding 1.15% will nearly double the trading intensity and if the volatility exceeds 2.61% either condition would have nearly tripled effect. Aggregate returns do not condition the overconfidence-trading link. These findings contribute to behavioral finance by suggesting that overconfidence is not static but intensified as strong performance and high volatility are observed. Practically, the indicators at the thresholds offer regulators early-warning indicators of speculative surges and offer investors risk management strategies even amid such risks. .